Making disciples in Croatia - Bohall, Jeremy (Array, 2019)
This project explores how the Evangelical Pentecostal Church (EPC) in Croatia is making disciples of Jesus Christ today. The goal is to demonstrate that despite the worldwide and local deficit in effective disciple making, the EPC has the resources and potential to live in obedience to the Great Commission. This has been shown by looking at the historical definition of a disciple, exegeting Matthew 28:16-20, exploring the proper context of disciple-making, and interviewing several members of the EPC. Upon examination, while there are multiple causes for the lack of disciples in Croatia, the primary problem is that of what will be called naive disobedience. It will be argued that local churches in the EPC have not been taught how to properly make disciples. By presenting the importance of teaching, relationships and practicing the spiritual disciplines, it will be demonstrated that a solution to the lack of disciple-making exists within the EPC.